ADAPTASI KEBIASAAN BARU GUEST SERVICE AGENT DI MASA PANDEMI COVID 19 PADA HOTEL BERBINTANG DI SULAWESI SELATAN - Kurnia Yusniar Rahman (Universitas Hasanuddin, 2021)
This study aims to (1) find out the services of guest service agents during the Covid 19 Pandemic and (2) assess the readiness of adaptation to new habits of guest service agents in the Covid 19 Pandemic Period at five-star hotels in South Sulawesi. Collecting data from this study was carried out using the following techniques: interviews, documentation, and observation, and data analysis was carried out using descriptive qualitative methods. The results of this study indicate that the service of guest service agents during the new normal period in several hotels is good, but the readiness of officers and the provision of facilities is not yet fully implemented as seen from the Guidelines for the Implementation of Hygiene, Health, Safety, and Environmental Sustainability or what is usually called the Cleanliness Implementation Guidelines, Health, Safety and Environmental Sustainability (CHSE) in implementing health protocols.